1992
DOI: 10.1073/pnas.89.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal IgM rheumatoid factors bind IgG at a discontinuous epitope comprised of amino acid loops from heavy-chain constant-region domains 2 and 3.

Abstract: A combination of site-directed mutagenesis and exon exchange has been used to further define the structure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 32 publications
2
51
1
Order By: Relevance
“…Later it was shown that many RA-derived RFs bind IgG at a discontinuous epitope comprising residues from both the CH2 and CH3 regions [35]. Studies in Waldenström's macroglobulinemia patients revealed that at least three regions, two from CH2 and one from CH3, contribute to the binding epitope [36]. Amongst a panel of monoclonal RFs, Mageed et al [37] observed four specificity profiles, namely reactivity with an epitope expressed on (a) all IgG subclasses, (b) IgG1, IgG2, IgG4 and certain IgG3 molecules, (c) IgG1, IgG2 and IgG4, but not IgG3, (d) some but not all IgG within the subclasses.…”
Section: Specificity Of Anti-ig Absmentioning
confidence: 99%
“…Later it was shown that many RA-derived RFs bind IgG at a discontinuous epitope comprising residues from both the CH2 and CH3 regions [35]. Studies in Waldenström's macroglobulinemia patients revealed that at least three regions, two from CH2 and one from CH3, contribute to the binding epitope [36]. Amongst a panel of monoclonal RFs, Mageed et al [37] observed four specificity profiles, namely reactivity with an epitope expressed on (a) all IgG subclasses, (b) IgG1, IgG2, IgG4 and certain IgG3 molecules, (c) IgG1, IgG2 and IgG4, but not IgG3, (d) some but not all IgG within the subclasses.…”
Section: Specificity Of Anti-ig Absmentioning
confidence: 99%
“…We studied monoclonal RFs derived both from synovial and peripheral B cell lines from RA patients and found that they have diverse antigenic specificities not found among malignancy-associated RFs (22,23). The basis for these differences might relate to usage ofdiverse genes and gene combinations to encode RFs or, alternatively, to the presence of somatic mutations in the RFs from RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, healthy individuals have circulating B cells with specificity for autoantigens (20,21). Autoantibodies exist that recognize different domains of Igs, such as the Fc domain-binding rheumatoid factor (22). There is also evidence for autoantibodies that recognize proteolytically cleaved Igs in the form of Fab and F(abЈ) 2 (23)(24)(25).…”
mentioning
confidence: 99%